Once-daily aminoglycoside therapy: potential ototoxicity. - Singer, C (1996)
Current data indicate that once-daily aminoglycoside therapy is as efficacious as traditional multiple daily dosing and equally or less toxic. Our experience with once-daily gentamicin, 6 mg/kg of body weight led to a 10% (3 of 33 patients) occurrence of documented ototoxicity after prolonged aminoglycoside exposure.